PEMANFAATAN PATI SINGKONG KARET (Manihot glaziovii) UNTUK PRODUKSI BIOETANOL FUEL GRADE MELALUI PROSES DISTILASI-DEHIDRASI MENGGUNAKAN ZEOLIT ALAM - Nadia Zahrotul Firdausi; Nugraha Bayu Samodra; H Hargono (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Bioethanol is an alcohol substance which can be obtained by biomass fermentation process by microorganism.Fuel grade bioethanol must obtain purity higher than 99,5% (w/w) . The making of fuel grade bioethanol through several processes, hydrolysis, fermentation, and purification. Bioethanol can be produced from starch material such as singkong karet (Manihot glaziovii) which has no economic value as a food product. Before fermentation process, it must be hydolyzed first to convert starch into glucose by α-amylase dan glucoamylase enzyme. Fermentation process use Saccharomyces cerevisiae from fermipan yeast to convert glucose into ethanol. Ethanol purification use distillation process followed by dehydration process. Dehydration process use natural zeolite to break azeotrop composition of ethanol-water at 95,63% (w/w),in order to obtain fuel grade ethanol. The objectives of this research are to examine starch conversion into glucose by the effect of glucoamylase enzyme added, glucose conversion into ethanol by the effect of fermipan yeast added, and purity of ethanol obtained by the effect of zeolite used. This research results that the highest starch conversion is 42,20% in addition of glucoamylase enzyme 0,20% (v/v); the highest glucose conversion is 77,93% in addition of fermipan yeast 1,5% (w/v); and the highest purity of ethanol obtained is 99,73% (w/w) by using zeolite as adsorben 90% (w/v), which is accepted as fuel grade bioethanol.